Analisis Sistem Kerja Asyncronus Transfer Mode (ATM) Pada Aplikasi Canva - Rahima Mahabbah; Ryan Adam Hidayatullah; Gelen Veranda Deanda; Didik Aribowo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Asynchronous Transfer Mode (ATM) is a network technology designed to support high-speed data transfer by utilizing small fixed-size data packets called cells. This study aims to analyze the implementation and performance of ATM in the context of the Canva application, a web-based graphic design platform. The study includes a theoretical review of ATM's working principles, advantages, and limitations, as well as the network performance analysis methods used.In this research, we examine how ATM can optimize data transmission in the Canva application, considering the importance of network speed and efficiency in ensuring an optimal user experience. The analysis results show that ATM can provide the high transfer speeds and stability required by the Canva application, especially in managing complex and large-sized graphic data.The conclusion of this study confirms that the implementation of ATM technology in web-based applications like Canva can significantly enhance network performance. This study also offers important insights for further development in integrating advanced network technologies for internet-based applications to support increasing data demands.